Comparative Pathology of the Peripheral Nervous System. Issue 1 (January 2021) - Lanigan, Lisa G.; Russell, Duncan S.; Woolard, Kevin D.; Pardo, Ingrid D.; Godfrey, Virginia; Jortner, Bernard S.; Butt, Mark T.; Bolon, Brad
The peripheral nervous system (PNS) relays messages between the central nervous system (brain and spinal cord) and the body. Despite this critical role and widespread distribution, the PNS is often overlooked when investigating disease in diagnostic and experimental pathology. This review highlights key features of neuroanatomy and physiology of the somatic and autonomic PNS, and appropriate PNS sampling and processing techniques. The review considers major classes of PNS lesions including neuronopathy, axonopathy, and myelinopathy, and major categories of PNS disease including toxic, metabolic, and paraneoplastic neuropathies; infectious and inflammatory diseases; and neoplasms. This review describes a broad range of common PNS lesions and their diagnostic criteria and provides many useful references for pathologists who perform PNS evaluations as a regular or occasional task in their comparative pathology practice.